(3GdbGehS GdeMjWs - (3GdajQhRBHGOj, eMeO Hf jYbhH Hf eMeO,s 729-817 (3g`(B.s ((3HjQhJ (B:s (3OGQ fhHjdjS,s, 2006)
(3jMJhj gPG GdbGehS Ydi eYGfj GdcdeGJ GdYQHjI(B.s
(3jTJed Ydi cTGa eQJH gLGFjG HGdMQha GdYQHjI(B.s
Keywords: (3GddZI GdYQHjIs -- (3eYGLes